Bifurcations in Dynamic Systems with Dry Friction - Stelter, Peter; Sextro, Walter (Bifurcation and Chaos: Analysis, Algorithms, Applications)
Dry friction is a main factor of self-sustained oscillations in dynamic systems. The mathematical modelling of dry friction forces result in strong nonlinear equations of motion. The bifurcation behaviour of a deterministic system has been investigated by the bifurcation theory. The stability of stationary solutions has been analyzed by the eigenvalues of the Jacobian. Period doublings and Hopf-bifurcations as well as turning points could be determined with the program package BIFPACK. Phase plane plots of periodic and chaotic motions have been shown for a better understanding of the bifurcation diagrams. Both, unstable branches and stable coexisting solutions have been calculated. Several jumping effects, which are typical for nonlinear systems, have been found.

Visualization in the Analysis Cycle of Observational Data, in Analyzing and Modeling Data and Knowledge - Domik, Gitta; Mickus, KD (Proceedings of the 15th Annual Conference of the "Gesellschaft für Klassifikation e.V." University of Salzburg)

A Look-Ahead Technique for Large Vocabulary Continuous Speech Recognition - Haeb-Umbach, Reinhold; Ney, Hermann (EUROSPEECH, Genova)
In a large vocabulary continuous speech recognition task the search for the "best" (in the maximum-a-posteriori sense) word sequence is the most (computing) time consuming part of the system. End-of-word hypotheses are created almost every time frame. With a stochastic language model every lexicon entry is an admissible successor candidate. By using a "fast match" module which scores the word candidates according to their acoustic feasibility ahead of the current time frame, the search cost can be considerably reduced. Only the fraction of the words with favourable fast match scores will be further processed in the detailed match, where the likelihood of a segment of acoustics given the word model is computed. We derive a novel word selection strategy which is "consistent" in the sense that it introduces no additional decoding errors and which still reduces the search space by a factor of 2 - 3 compared to standard Viterbi beam search. Giving up the consistency requirement, pruning strategies can be deduced which further reduce the search effort significantly: the size of the word startup list is reduced to 2% - 4% of its original size with a modest increase in error rate by l%-2%.

Synthese vollständig testbarer Schaltungen - Hellebrand, Sybille

Ernst Schröder und die ,pasigraphischen Systeme‘ von Peano und Peirce - Peckhaus, Volker (Modern Logic)
Modern Logic 1 (1990–91), H. 2/3 (Winter 1990/91) Abstract: Historia Mathematica 18 (1991), #18.4.67 (I. Anellis). Rezensionen: Studia Logica 51 (1992), 150–151 (R. Murawski); MR 92e:03002 (I. Angelelli); Zbl. Math. 735.01007 (I. Grattan-Guinness).

Discrete-Time Flux Observer for PWM Inverter-Fed Induction Motors - Böcker, Joachim; Janning, Jörg (EPE’91, Florence, 1991)

Discrete-time model of an induction motor - Böcker, Joachim (European transactions on electrical power)

Kurt Grelling und der Logische Empirismus [Abstract] - Peckhaus, Volker (Mitteilungen des Instituts für Wissenschaft und Kunst 46 (1991), Nr. 2 (= „Wien — Berlin — Prag. Der Aufstieg der wissenschaftlichen Philosophie. Internationales Symposion aus Anlaß der Centenarien von Rudolf Carnap (1891–1970), Hans Reichenbach (1891–1953), Edgar Zilsel (1891–1944)“))

Logic in Transition: The Logical Calculi of Hilbert (1905) and Zermelo (1908) [Abstract] - Peckhaus, Volker (Abstracts of the 9th International Congress of Logic, Methodology and Philosophy of Science, Uppsala, August 7–14, 1991, Bd. 2: General Philosophy of Science. Sections 6–9)

Ernst Schröder und die logizistische Begründung der Mathematik [Abstract] - Peckhaus, Volker (Deutsche Mathematiker-Vereinigung. Jahrestagung 15.–20.9.1991 in Bielefeld. Vortragsauszüge)